BÁRBARA CARINE SOARES PINHEIRO: CHEMIST, MOM, NORTHEAST AND MILITANT BLACK - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Bárbara Carine Soares Pinheiro was born in 1987, on the suburbs of Salvador. She is the great-granddaughter of Vicença, the granddaughter of Djanira Soares and the daughter of Teresinha Soares de Jesus. She grew up free on the streets of her neighbourhood - she still remembers very well feeling the smell of red clay after rainfall. She graduated in 2010 at the Federal University of Bahia (UFBA) and obtained the title of Master’s Degree in 2012 and PhD in 2014. She is a professor at the Institute of Chemistry at UFBA. Today, Bárbara defines herself as: critical-decolonial researcher, anti-racist, north-eastern feminist, pagodeira, bisexual, cis black woman, mother. On the other hand, she does not define herself: she opens up in a constant movement of self-building or, perhaps, or yet to be built.